Dragonflies of Cusuco National Park, Honduras; checklist, new country records and the description of a new species of Palaemnema Selys, 1860 (Odonata: Platystictidae) - Jocque, Merlijn; Garrison, Rosser (Zootaxa, 2022)
The odonate fauna of Honduras is poorly documented. Based on 10 years of observations and collections we present an overview of dragonflies from cloud forests in Cusuco National Park, northwestern Honduras. A total of 44 species were reported including at least seven new country records for Honduras we include ecological observations for most species. A new species of Platystictidae (Palaemnema lorae Jocque & Garrison, n. sp. Holotype ♂: HONDURAS: Cortés Dept., CNP, Cantiles, Trail 5, small river close to camp, N15.513457 W88.241681; 1846m, 23 June 2012 collected by Merlijn Jocque, field code: BINCO_HON_12_047, in RBINS) is described and illustrated.